2018
DOI: 10.1101/305755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Analysis Reveals a Shared Immune Signature in CASP8-Mutated Carcinomas with Varying Correlations to Prognosis

Abstract: Background: Sequencing studies across multiple cancers continue to reveal the spectrum of mutations and genes involved in the pathobiology of these cancers. Exome sequencing of oral cancers, a subset of Head and Neck Squamous cell Carcinomas (HNSCs) common among tobacco-chewing populations, revealed that ~34% of the affected patients harbor mutations in the CASP8 gene. Uterine Corpus Endometrial Carcinoma (UCEC) is another cancer type where about 10% cases harbor CASP8 mutations. Caspase-8, the protease encode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…CASP8 is a protease involved in the extrinsic apoptotic pathway and also a negative modulator of programmed cell necrosis [63]. Mutant CASP8 HNSCs had distinctive characteristics of genes associated with inflammation and the immune response and were rich in immune cell infiltration [64]. It has been reported that inactivating mutations of NSD1 define an HNSC intrinsic subtype with significant DNA hypomethylation [65].…”
Section: Discussionmentioning
confidence: 99%
“…CASP8 is a protease involved in the extrinsic apoptotic pathway and also a negative modulator of programmed cell necrosis [63]. Mutant CASP8 HNSCs had distinctive characteristics of genes associated with inflammation and the immune response and were rich in immune cell infiltration [64]. It has been reported that inactivating mutations of NSD1 define an HNSC intrinsic subtype with significant DNA hypomethylation [65].…”
Section: Discussionmentioning
confidence: 99%
“…Great progresses have been attained in the past few years, making it possible to recognize novel molecular therapeutic targets within the microenvironment of EC [12]. At the same time, several immune-related factors have been identi ed to predict patient prognosis, which emphasizes the signi cance of certain immune status on EC outcomes [13]. Nonetheless, the vast majority of existing studies are pre-clinical basic experiments or have limited available clinical information, while study with a large sample size has not been carried out so far [14].…”
Section: Introductionmentioning
confidence: 99%